Transforming ABC Co- Through Lean Management & Agile Manufacturing - Singh, Hari (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2012)
ABC co. was established in Delhi in 1980, which produced electrical switchgears & appliances. The company had manual operations initially; quality was not a thrust area having about 16% process rejections. The demand for electrical appliances/switchgears was rising with increase in urbanization/ construction activities. The warranty return was as high as 6% and more competitors entered in the market making it difficult to improve sales. After brainstorming session, management implemented various techniques of TQM tools (5S, SQC, TPM, etc.). Investment in new technology including installation of few new machines and few low cost automation of equipment was made.ABC co. expected the payback period of three years for the new installed capacity. The internal rejections came down and as also cost and thereby market demand rose significantly. The major contribution was: a) Improving quality, b) Inventory reductions, c) BOM cost reduction, d) reduced order to supply time.